Integration of biomimicry into science education: biomimicry teaching approach - Coban, Merve; Costu, Bayram (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2023)
This study aims to integrate biomimicry into science education by proposing a teaching approach for primary school students. An action research approach was used. The developed 'Biomimicry Teaching Approach' was applied in a 5(th) grade classroom in a public school in Turkey where one of the authors is a teacher. According to this approach, the students firstly were presented with different kinds of organisms to develop the ability to observe organisms and understand therelationship between structure and function. Secondly, they were introduced to the biomimicry concept with several examples. Finally, the students were engaged with a 'Biomimicry Design Model'. At the end of the biomimicry lessons, the students designed their models through drawing and modelling inspired by the organisms. The effects of the 'Biomimicry Teaching Approach' on student designs were analysed. Results showed that the 5(th) grade students mostly produced their own design ideas inspired by the organisms presented throughout the biomimicry lessons. The students' attempts to create different designs by taking inspiration from the organisms in nature and considering the function behind the physical structure of the organisms showed that students can produce creative and applicable design ideas inspired by nature when they are introduced to biomimicry through 'Biomimicry Teaching Approach'.
Keywords: Biomimicry; nature-inspired design; biomimicry Teaching Approach; biomimicry Design Model; science education; Life Sciences & Biomedicine - Other Topics; Education & Educational Research